Assessment of knowledge, attitude and practice of fixed-dose combinations amongst attending physicians and residents: a cross-sectional evaluation - Dhyuti Gupta; Prithpal Singh Matreja; Shilpa Patrick; Meenu Thomas; Pooja Agarwal; Preeti Singh (Drugs in Context, 2024)
Background: Fixed-dose combinations (FDCs) were brought into the market with the intent of providing benefits primarily to patients and physicians. Nevertheless, despite their multiple advantages, they have their own set of drawbacks, especially regarding irrational FDCs. If physicians continue to prescribe them, prohibiting their sale would become all the more challenging. This cross-sectional survey study was planned to comprehend the level of knowledge, attitude and practice of physicians regarding such FDCs at a tertiary care teaching institute of western Uttar Pradesh, India.